Cardiac autonomic dysfunction in chronic stroke women is attenuated after submaximal exercise test, as evaluated by linear and nonlinear analysis. Issue 1 (December 2015) - Francica, Juliana; Bigongiari, Aline; Mochizuki, Luís; Scapini, Kátia; Moraes, Oscar; Mostarda, Cristiano; Caperuto, Erico; Irigoyen, Maria; De Angelis, Katia; Rodrigues, Bruno
Abstract Background We evaluated cardiac autonomic modulation in women with chronic ischemic stroke (at least 4 years post-stroke) at rest and in response to submaximal exercise test. Methods Fourteen post-stroke women (S group) and 10 healthy women (C group) participated in this study. Autonomic modulation (using linear and nonlinear analysis), blood pressure and metabolic variables at rest were evaluated immediately after the exercise test and during the recovery period (20 min). All participants underwent submaximal exercise test on cycle ergometer with gas analysis. Results At rest, the S group displayed higher lactate concentration, systolic (SBP) and diastolic blood pressure (DBP) values when compared to C group. Furthermore, the S group had lower heart rate variability (HRV) in time domain (SDNN: S = 30 ± 5 vs. 40 ± 8 ms; rMSSD: S = 14 ± 2 vs. C = 34 ± 3 ms), decreased high frequency band of pulse interval (S = 8.4 ± 2 vs. 33.1 ± 9 %) and 2V pattern of symbolic analysis (S = 17.3 ± 1 vs. 30 ± 3 %) (both indicators of cardiac vagal modulation) when compared to C group. Immediately after exercise, S group presented higher values of lactate, SBP, DBP and double product when compared to C group, as well as decreased heart rate recovery (HRR) measured at the first, second and third minutes. At recovery time, all HRV parameters in time and frequency domains improved in the S group; however, HF band remained lower when compared to C group. Conclusions After the exercise test, women with chronic stroke presented reduced heart rate variability, reduced cardiac vagal modulation, as well as reduced HRR, while displayed an improvement of heart rate variability and cardiac vagal modulation when compared to their baseline. These results reinforce the importance of a physically active lifestyle for cardiovascular autonomic disorders observed in chronic stroke women.